Mediation effects of organisational commitment on relationship between personality traits and turnover intention at a private university in Malaysia - Ng, Chee Heng (2013)
Abstract: The management of the Private Higher Educational Institutions (PHEIs) in Malaysia is a relatively new area of study, gaining significance in the last 20-30 years. Within the PHEIs, researchers had discovered that a number of factors and management concepts co-existed and inter-related, and simultaneously these variables influence the policy formation, leadership styles and principles, future planning, staff mobility etc. of the institutions, where these organizations are basically profit-oriented business organizations. This study investigated the mediation effects of the organizational commitment components on the relationships between the Big Five Personality factors and the turnover intention of the academic employees of a private university at the Klang Valley,Malaysia. Structural Equation Modelling techniques were used to conduct a simultaneous test on the best fitting structural model developed through the measurement model. The model proposed relationships between all the five personality trait factors, as the independent variables, and turnover intentions, as the dependent variable; to be mediated by three components of organizational commitments. Path analysis conducted on the data found that four personality trait factors were statistically significant predictors of turnover intention; with Openness to experience (O) and Neuroticism (N) positively related while Conscientiousness (C) and Extraversion (E) were negatively related to the dependent variable. For organizational commitment components, all three components were found to correlate negatively to turnover intentions. The mediation effects of the organizational commitment components on the relationship were analysed using the SEM bootstrapping techniques; with a powerful 1000 bootstrap samples. Analysis results showed that while the continuance commitment partially mediated the relationship between Openness to experience (O) and Turnover intention (TI); both continuance and normative commitments fully mediate relationships between Conscientiousness (C) and Turnover Intention (TI), and Neuroticism (N) and Turnover Intention (TI). Mediation effects by organizational commitment components on relationships between Extraversion (E) and Turnover Intention (TI), Agreeableness (A) and Turnover Intention (TI) were not supported by the data.